KAJIAN LITERATUR: PENDIDIKAN SEKSUAL DAN GENDER DALAM PERSPEKTIF PARENTING ISLAM - Fadiza Syafira; Najwa Mahfuza; Mutiara Alya Hasyim; Masganti Sitorus (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Sexual and gender education is an important issue in child development that often sparks debate in society, especially when linked to religious and cultural values. In the era of globalization, children are exposed to a rapid and open flow of information through both mass media and digital platforms. This situation makes it easier for children to access information related to sexuality and gender issues that may not be appropriate for their developmental stage. Therefore, providing sexual and gender education from an early age has become an urgent need to ensure that children develop a proper, healthy, and morally grounded understanding. Gender refers to the differences in roles, responsibilities, functions, and social constructions between men and women, shaped by culture, environment, and social systems. Gender differs from sex (biological differences), as sex is innate and determined by God from birth (such as being male or female), while gender is more of a social concept that can change according to societal contexts. In Islam, the distinction between men and women is a form of fitrah (divine nature) that must be respected. From an Islamic perspective, child education encompasses not only cognitive aspects but also moral dimensions. Islamic parenting views the role of parents as guiding children to grow into faithful individuals with noble character who can preserve their natural human disposition (fitrah).